Preliminary Memorandum on the Fourth Five Year Plan Gujarat State February 1965 - Government og Gujarat (Government of Gujarat, 1965)
The Preliminary Memorandum on the Fourth Five-Year Plan (1965–1970) for Gujarat State presents a comprehensive framework aimed at addressing the socio-economic challenges that emerged following the formation of the state in 1960. With a population exceeding 20 million according to the 1961 census and a significant proportion of the workforce dependent on agriculture, the memorandum emphasizes the urgent need to strengthen agricultural productivity, expand irrigation facilities, and improve rural livelihoods. The proposed plan outlay of ₹470 crores, nearly double the allocation of the Third Plan, reflects the state’s commitment to accelerated development across multiple sectors. A substantial portion of the investment, approximately 52 percent, is allocated to agriculture and irrigation, including major projects such as Ukai, Narmada, and Kadana, with the objective of increasing food production and improving water management. Industrial development forms another key component of the plan, focusing on diversification beyond the textile sector and promoting industries such as chemicals, engineering, and petrochemicals while also encouraging the growth of small-scale industries and industrial estates in backward regions. The memorandum also highlights the importance of strengthening power generation capacity to meet the projected demand of 1,050 MW by 1970–71, proposing expansions such as the Dhuvaran Extension Project and gas turbine installations to bridge the anticipated energy deficit. In addition, rural electrification initiatives aim to expand electricity access to villages, thereby supporting agricultural modernization and rural industries. Infrastructure development, particularly improvements in road transport and communication networks, is recognized as essential for facilitating economic activity and regional connectivity, with significant financial allocations for road expansion. The plan also addresses employment generation by forecasting the creation of nearly nine lakh jobs through public and private sector initiatives, while social services including education, healthcare, and family planning are emphasized to improve living standards and human development. Despite financial constraints and a projected budget deficit requiring central government assistance, the memorandum outlines a balanced and integrated strategy designed to promote agricultural growth, industrial expansion, infrastructure modernization, and social welfare. Overall, the Fourth Five-Year Plan for Gujarat represents a strategic effort to achieve sustainable and inclusive economic development while reducing regional disparities and strengthening the state’s long-term economic foundation.
Government of Gujarat General Administration Department (Planning)
Government of Gujarat General Administration Department (Planning)
Keywords: Fourth Five-Year Plan Gujarat; State Development Planning; Agricultural and Irrigation Development; Industrial Diversification Strategy; Power Generation Expansion; Rural Electrification Programme; Infrastructure and Transport Development; Employment Generation Strategy; Socio-Economic Development Gujarat; Investment and Resource Allocation; Backward Region Development; Education and Social Services